Val och valregler inom kooperativa företag - Essen, Carl-Fredrik von (2006)
This work summarises some of the new choice theories and compares them with the neo-classical theories. It will deal with choice behaviour in situations with complex choice, such as may be encountered by board members or members of a co-operative company. The thesis discusses how choice may change if the rules of choice change. The hypothesis that people will vote differently depending on whether they choose a desired alternative or remove the undesired alternatives will be tested.